The safety and efficacy of adjunctive 20-Hz repetitive transcranial magnetic stimulation for treatment of negative symptoms in patients with schizophrenia: A double-blinded, randomized, sham-controlled study - Singh, Swarndeep (Indian J Psychiatry, 2020)
BACKGROUND: Repetitive transcranial magnetic stimulation (rTMS) is a promising treatment strategy for negative symptoms. However, the evidence for its efficacy is mixed, with contradictory results between studies due to lack of consensus about the optimal stimulation parameters. AIM: The present study was planned to assess the safety and efficacy of 20-Hz rTMS over left dorsolateral prefrontal cortex (Lt-DLPFC) with more robust stimulation parameters for adjunctive treatment of negative symptoms in patients with schizophrenia. MATERIALS AND METHODS: Thirty patients with negative symptoms of schizophrenia (Positive and Negative Syndrome Scale [PANSS] negative subscore ≥15) were randomized to receive a 4-week treatment with either real-rTMS (n = 15) or sham-rTMS (n = 15). The study outcomes were assessed at baseline, after 5(th) and 20(th) rTMS sessions with PANSS, Scale for the Assessment of Negative Symptoms (SANS), Calgary Depression Scale for Schizophrenia, Clinical Global Impressions-Severity of illness scale, and rTMS side-effect checklist. RESULTS: There was significantly greater reduction in negative symptoms assessed by SANS score in the real rTMS group, compared with the sham rTMS group. There was no significant difference in the rate of side-effects reported between the two groups. The rTMS treatment was well-tolerated by all the patients, except one seizure episode reported in the active group. CONCLUSION: The high-frequency rTMS protocol was safe and well-tolerated, provided patients prone to developing seizure were excluded by baseline electroencephalography prior to starting of the treatment. The 20-Hz rTMS over Lt-DLPFC with more robust stimulation parameters (100% motor threshold and 40,000 pulses) might be an effective augmentation strategy for the treatment of negative symptoms in schizophrenia.